2014
DOI: 10.1161/circheartfailure.113.000672
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin 1–7 Ameliorates Diabetic Cardiomyopathy and Diastolic Dysfunction in db/db Mice by Reducing Lipotoxicity and Inflammation

Abstract: Background-The angiotensin-converting enzyme 2 and angiotensin-(1-7) (Ang 1-7)/MasR (Mas receptor) axis are emerging as a key pathway that can modulate the development of diabetic cardiomyopathy. We studied the effects of Ang 1-7 on diabetic cardiomyopathy in db/db diabetic mice to elucidate the therapeutic effects and mechanism of action. Methods and Results-Ang 1-7 was administered to 5-month-old male db/db mice for 28 days via implanted microosmotic pumps. Ang 1-7 treatment ameliorated myocardial hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
129
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 52 publications
10
129
0
Order By: Relevance
“…Consistent with these results, Mori et al 35 showed that Ang-(1-7) infusion prevented PKCα elevation in db/db mice.…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with these results, Mori et al 35 showed that Ang-(1-7) infusion prevented PKCα elevation in db/db mice.…”
Section: Discussionsupporting
confidence: 52%
“…Unoxidized FA accumulation in cardiac myocytes impairs energy metabolism and aggravates mitochondrial dysfunction, ROS overproduction, and lipoapoptosis (Drosatos & Schulze, 2013; Rodrigues et al., 1995). Several recent studies concluded that strategies to minimize ectopic fat accumulation and lipotoxicity have direct cardioprotective effects (Mori et al., 2014; Yang et al., 2007). To the best of our knowledge, the present study is the first to revealed that both exendin‐4 and saxagliptin significantly reduced lipid content in CMs both in vivo and in vitro by controlling the PPARa‐CD36 pathway, which is a major regulatory signal in cardiac FA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Dried samples were dissolved in 50 l of a 3:2 tert-butyl alcohol-Triton X-100-methyl alcohol mixture. TAG levels were quantitated colorimetrically as glycerol using an enzymatic assay (Wako Pure Chemical Industries, Osaka, Japan) (32). Plasma TAG levels were also quantified colorimetrically using the same enzymatic assay.…”
Section: Methodsmentioning
confidence: 99%